Online collaborative Padlet-mediated learning in health management studies - Naamati-Schneider, Lior; Alt, Dorit (Frontiers in Psychology, 2023)
The Padlet interactive platform constitutes a virtual online board on which users can post various types of multimedia content, such as documents, questions, comments, images, video clips, and audio clips. This platform has gained popularity in higher education yet remains ancillary in the fields of medical education and medical management. This case study sought to initially design an intervention program that employs online collaborative learning enabled by Padlet and to assess how Health Management students perceived the activity and its ramifications for their learning. 85 students’ reflective journals were content analyzed, revealing five main categories: (1) user experience of the platform; (2) visuality and visibility of the platform; (3) collaborative learning and OCL; (4) active online learning and student engagement; and (5) cognitive flexibility. This study emphasizes the importance of incorporating digital tools in education, particularly the use of the Padlet platform to facilitate collaborative learning and improve the quality of teaching and learning. It demonstrates that Padlet-mediated online collaborative learning can be an effective digital learning tool because of its ease of use and ability to accommodate both pedagogical and technological challenges.